Этнофразеология как современное научное направление лингвистики - Савченко, Л.В. (Культура народов Причерноморья, 2014)
В статье исследуется взаимодействие языка и культуры в контексте синтеза этнолингвистики и фразеологии, которое определяет самостоятельное направление исследований – этнофразеологию. Выделяются и анализируются основные единицы этнофразеологии – этнофразеологизмы, этнофразеологизированные сочетания, перформативные этнофразеологические единицы, которые генетически связаны с культурой и составляют целостный фрагмент фразеологической картины мира. У статті досліджується взаємодія мови та культури в контексті синтезу етнолінгвістики і фразеології, яка визначає самостійний напрям досліджень – етнофразеологію. Виділяються і аналізуються основні одиниці етнофразеологіі – етнофразеологізми, етнофразеологізовані сполучення, перформативні етнофразеологічні одиниці, які генетично пов'язані з культурою і складають цілісний фрагмент фразеологічної картини світу. The paper investigates the interaction between language and culture in the context of synthesis of ethnolinguistics and phraseology, which determines the direction of independent research – ethnophraseology. The main units of ethnophraseology are defined and analyzed – ethnophraseologisms, ethnophraseologized combinations, performative ethnophraseological units, that are genetically linked to the culture and are an integral piece of phraseological picture of the world. Ethnophraseological unit (EPU) is a special kind of semantically indivisible stable combinations of words, ethnically and culturally conditioned mental formations, the structure of which contains a component of culture, expressed by ethnolexeme, or scenario of the image of the unit reflects actional act or representations that is inherent to ethnos, the origin of which is associated with the rituals, customs, traditions, beliefs, mythology, history. In the formation of the semantics of many EPU, ethno-cultural views and beliefs, information about rituals, customs, and various magic tricks of verbal and actional nature play a decisive role. The term ethnocomponent refers to culturally or ethnically marked nominateme in the structure of EPU, which is related to the ethnic material or spiritual culture of the people and gives a distinct national character to the notion. Among the investigated material allocate ethnophraseologized combination – one endowed with features of reproducibility and stability, in the image of which fragments of traditions, rituals, customs, forms of leisure or their names are depicted. We use term performative to refer to the stable combinations with the structure of actions, forming statements of communicative intent (the action takes place simultaneously with the pronunciation of the action), which reflect the magic formulas of oaths, curses or etiquette statements use the term performative. Attention to ethnic and cultural reality in the study of linguistic units is a priority trend of the development of ethnolinguistics, as evidenced by an active strengthening of the position of ethnophraseology.